Ductility and Damping Characteristics of PVA-FRC Beam Elements. Issue 11 (November 2015) - Noushini, A.; Samali, B.; Vessalas, K.
The structural behaviour of reinforced concrete beams incorporating polyvinyl alcohol (PVA) fibres is investigated in this study. A total of 10 reinforced concrete beams have been tested in order to investigate how the structural characteristics (i.e. ductility, energy dissipation capacity and damping ratio) of concrete beam elements are affected by addition of a certain amount of PVA fibres into the concrete. The structural properties and behaviour of PVA-FRC beams were assessed under the action of both monotonic and cyclic loads. Four-point static flexural, three-point cyclic and impact resonant frequency tests were conducted on PVA-FRC beams and results of which are compared with conventional reinforced concrete (RC) beams. Experimental results show that PVA fibre addition to the mix, generally, improves the ductility and damping ratio of the elements. Furthermore, PVA-FRC beams showed higher stiffness degradation rate and higher capacity to maintain their stiffness during the test.